Cases on enterprise information systems and implementation stages learning from the Gulf region - Albadri, Fayez Ahmad, 1958- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book focuses on the Gulf region and its lead on enterprise systems adoption (which has exceeded those in many developed countries) by highlighting experiences implementing EIS, delivering a comprehensive, multi-perspective account of EIS issues, and exploring the concerns, risks, and critical success factors of EIS for a variety of organizations"--Provided by publisher.